From Quantity to Quality: Changes in Information Provision in a Medium-sized Dutch University Library - Laeven, A.H. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
This paper uses the library of the University of Nijmegen as a starting point; however, much of the information provided also applies to other Dutch libraries.